Innovative Technologies and Climate Change Adaptation and Mitigation in Pakistan (Journal of Asian Development Studies, 2023)
Pakistan is particularly vulnerable to the effects of climate change, which is a worldwide threat with far-reaching effects. To meet the different climate difficulties Pakistan faces, this research comprehensively investigates the role of innovative technologies in climate change adaptation and mitigation in Pakistan. As reliance on the Indus River system increases susceptibility, this study looks at how cutting-edge technologies improve adaptive capabilities. Case studies like the Green Line Bus Rapid Transit System and the Quaid-e-Azam Solar Park demonstrate their effectiveness in reducing the consequences of climate change. Analyzing the effects on the economy and environment highlights how affordable and emissions-free these technologies are. The study evaluates their efficacy critically while considering the consequences for the environment and finances. It also ends with suggestions for possible further study and advancement directions. This study provides important insights for international climate action by highlighting innovative technologies' critical role in protecting Pakistan against climate change.